Hybridization-induced resonances with high-quality factor in a plasmonic chipscale ring-disk nanocavity. Issue 6 (2nd November 2021) - Zhang, Zhaojian; Yang, Junbo; Han, Yunxin; He, Xin; Huang, Jie; Chen, Dingbo
ABSTRACT: Plasmonic resonators have drawn more attention due to the ability to confine light into subwavelength scale. However, they always suffer from a low-quality (Q) factor owing to the intrinsic loss of metal. Here, we numerically propose a plasmonic resonator with ultra-high Q factor based on plasmonic metal–insulator-metal (MIM) waveguide structures. The resonator consists of a disk cavity surrounded by a concentric ring cavity, possessing an ultra-small volume. Arising from the plasmon hybridization between plasmon modes in the disk and ring cavity, the induced bonding hybridized modes have an ultra-narrow full width at half maximum (FWHM) as well as ultra-high Q factors. The FWHM can be nearly 1 nm and Q factor can be more than 400. Furthermore, such a device can act as a refractive index sensor with an ultra-high figure of merit (FOM). This work provides a novel approach to design plasmonic high-Q-factor resonators and has potential on-chip applications such as filters, multi-spectral sensors and nanolasers.